Overeducation Among Swedish Youth - Yves Bourdet; Inga Persson (Lund University, School of Economics and Management, Department of Economics, 2008)
In this paper we analyse the changes that have taken place on the supply and demand sides of the Swedish labour market during recent decades, with particular focus on youths and the extent to which Swedish youths have become "overeducated". We first provide an overview of theoretical and measurement issues related to the concept of overeducation. Against this background we then survey some of the findings from earlier studies of the evolution of the demand and supply of skills in Sweden and of the extent and character of over- and undereducation. We then look specifically at overeducation among Swedish youths during their labour market entrance and early career and discuss the main issues related to overeducation that have been raised in the Swedish public debate.
Keywords: J21; J24; J31; 330; Overeducation; mismatch; wage-premium; youth employment; Sweden